2015
DOI: 10.1165/rcmb.2014-0477oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Plant Derivative Compound A on the Production of Corticosteroid-Resistant Chemokines in Airway Smooth Muscle Cells

Abstract: Preclinical models of human conditions including asthma showed the therapeutic potential of Compound A (CpdA), a dissociated glucocorticoid (GC) receptor (GRa) ligand. Whether CpdA inhibits GC resistance, a central feature of severe asthma, has not been addressed. We investigated whether CpdA modulates cytokineinduced GC resistance in human airway smooth muscle (ASM) cells. Healthy and asthmatic ASM cells were treated with TNF-a/IFN-g for 24 hours in the presence or absence of CpdA. ELISA and quantitative PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Particular GR-independent effects of CpdA have been reported before and are hence not restricted to DC. In a recent report studying airway smooth muscle cells, it was observed that CpdA inhibits the secretion of GC-resistant chemokines in a GR-independent manner59, again emphasizing benefit in absence of GR as a target of CpdA.…”
Section: Discussionmentioning
confidence: 93%
“…Particular GR-independent effects of CpdA have been reported before and are hence not restricted to DC. In a recent report studying airway smooth muscle cells, it was observed that CpdA inhibits the secretion of GC-resistant chemokines in a GR-independent manner59, again emphasizing benefit in absence of GR as a target of CpdA.…”
Section: Discussionmentioning
confidence: 93%
“…40 . Recently, another study 31 , using airway smooth muscle cells, reported a CpdA-induced expression of DUSP1, but not GILZ, both at the mRNA and protein level. Similar to our results, this occurred after a short time period, but in a steroid-resistant context, and was found to be GR-independent 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study 31 , using airway smooth muscle cells, reported a CpdA-induced expression of DUSP1, but not GILZ, both at the mRNA and protein level. Similar to our results, this occurred after a short time period, but in a steroid-resistant context, and was found to be GR-independent 31 . As a final explanation, CpdA may degrade more quickly in the cells as compared to the stable steroidal DEX, which is why a consideration of future treatment strategies based on the advantages of a dual GR ligand/modulator combination would definitely require stabler SEGRAM molecules 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we and others showed the implication of distinct pathways that regulate CXCL10 in ASM cells. Thus, in contrast to CCL5, CCL11 and CX3CL1, the production of CXCL10 in GC resistant conditions was the only chemokine which was (i) not repressed by a combination of fluticasone and KCa3.1 channel blockers , (ii) poorly sensitive to the natural derivative compound A and (iii) not involving IRF‐1‐dependent pathways . This differential action of GCs on CXCL10 expression was also reported in epithelial cells where fluticasone increased cytokine‐induced CXCL10 while inhibiting production of CXCL8 .…”
Section: Discussionmentioning
confidence: 52%